Abu Hilal al-‘Askari and His Contributions to the Field of Arabic Criticism - Mohamed Rady Mohamed Elpaz Elsheakh (Al-Jawhar : Journal of Arabic Language, 2025)
This research, entitled “Abū Hilāl al-ʿAskarī and His Contributions to the Field of Arabic Literary Criticism,” seeks to shed light on the critical contributions made by Abū Hilāl al-ʿAskarī to classical Arabic literary criticism, particularly through his seminal work Kitāb al-Ṣināʿatayn (The Book of the Two Arts). The central problem addressed in the study lies in the perception held by some scholars that Abū Hilāl was merely a transmitter of the views of his predecessors, lacking innovation or originality. Such a view, however, overlooks the significant intellectual efforts he made, especially when assessed within their proper historical context.The importance of this research lies in its objective and fair re-evaluation of Abū Hilāl al-ʿAskarī’s role and contributions to the field of classical Arabic criticism. It aims to reposition his work as a vital link in the chain of the development of Arabic critical thought. The study highlights both his theoretical and applied insights, thereby offering a more nuanced understanding of his critical legacy.Among the key findings of the study is that Abū Hilāl al-ʿAskarī not only compiled the opinions of earlier critics but also organized them according to refined aesthetic and critical sensibilities, enriching them with his own analytical insights and vast knowledge of Arabic poetic and prose traditions.The research is structured into an introduction and four main sections. The introduction outlines the topic and its significance. The first chapter is titled The Status of Abū Hilāl al-ʿAskarī in the History of Rhetoric and Criticism. The second chapter addresses Abū Hilāl al-ʿAskarī and Kalām (Islamic Theology). The third chapter :examines The Methodology of Abū Hilāl in Kitāb al-Ṣināʿatayn. The fourth is titled Abū Hilāl and His Critics. This is followed by the conclusion, which presents the key findings, as well as a section on recommendations, and finally the bibliography.